Berbagai Teori Motivasi Dalam Manajemen Pendidikan Islam - Rika Sartika; Johara Indrawati; Sufyarma Marsidin (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2022)
Motivation Theory's important role in the management process needs to be understood by educators to carry out various forms of action or assistance to the listeners. A person's attitude is determined by his desire to achieve a goal. Another term for will is motivation. Motivation is the motivation for a person to carry out activities to achieve his goals. The power of motivation for a person can change at any time. The change occurs because of satisfaction with the needs. Such satisfied needs have motivated one's attitude. This research is literature research, which is analyzed using the method of description, interpretation, and data analysis. The discussion in this study includes the notion of motivation, some motivational theories, types, and models of motivation, models of application of motivation theory in Educational Institutions, as well as several forms of motivation in Islamic Education. The results showed that Motivation in organizations is indeed very important to discuss in the study of organizational behavior. Because every personnel or member of the organization needs motivation, both from within oneself and from others, for that if someone has been encouraged or motivated, someone's performance will increase it will speed up the process of completing tasks and responsibilities at work.